Caracterização da comunidade planctônica em cultivo de camarão marinho, Litopenaeus vannamei (Boone, 1931) no Semiárido Potiguar - Lucena, Stefano Rafael (Universidade Federal Rural do Semi-Árido, 2018)
An experiment was carried out during 90 days in the aquaculture sector of UFERSA to evaluate the planktonic densities of various crops of the Litopenaeus Vannamei shrimp. The experimental design was entirely randomized, with five treatments and four repetitions each. The treatments were of the types, mono and polycultures, being monoculture of the marine shrimp L. Vannamei cultivated with well water (T-01); Monoculture of shrimp supplied with water from the cultivation of tilapia (T-02); Monocultivation of shrimp supplied with water from the cultivation of Tambatinga "Colossoma macropomum (female) x Piaractus Brachypomus (male)" (T-03); Polyculture of shrimp with Tilapias (T-04); Shrimp Tambatinga, (T-05). The stocking densities were of 50 Cameroon m³ for monocultures and ten prawns per m³ for the polycultures with two Tilapias m³ and a Tambatinga m³. The maintenance of the phytoplankton community was carried out with chemical fertilization based on urea and triple superphosphate and water renewal when necessary. Were placed on average ten centimeters of clay-sandy substrate at the bottom of the tanks and installed aeration type airlift. In relation to the density phytoplankton the algae were those that showed greater expressiveness, being recorded a maximum value of 1,883.5 cells per milliliter, with the genus Microcystis, in the polycultivation shrimp x Tambatiga (T-05). The Chlorophyceae group was the least highlighted in terms of the number of cells/ml presenting maximum values of 16.5 cells/ml of the genus Oocistis, in the polyculture of Shrimp x Tambatinga (T-05). During the study, organisms belonging to the five Zooplanctônicos groups were recorded as follows: Copepoda, Cladocera, Nematoda, Ostracoda and Rotifera. The copepods of the Sub-order Calanoida were the most representative in the Zooplanctônica community with occurrence in all the samples studied. Among the Zooplanctônicos organisms, were also observed, nauplii of Copepoda and Efípios of Cladocera. In the two systems of cultivation monoculture and polycultivation of the marine shrimp, Litopenaeus Vannamei occur modifications in the natural palmerina community.
Monografia
Keywords: Organismos planctônicos; Oreocrhomis niloticus; Litopenaeus vannamei; Aquicultura; Planktonic organisms; White spot syndrome virus – WSSV; Oreocrhomis niloticus; Litopenaeus Vannamei; Aquaculture; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA